Management of Productive Zakat, Infaq, Shadaqah Funds Through Linkage Program In Covid-19 Pandemic Era - Gardina Aulin Nuha; Norita Citra Yuliarti; Yuli Nartati (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2022)
Optimization of zakat collection will be achieved if zakat management organizations such as BAZNAS Regency need to improve the quality of zakat management by increasing the quality of services, transparency and accountability of financial reports. Distribution of zakat in the form of productive funds by BAZNAZ must be distributed quickly and accurately so that the community, especially those affected by the Covid-19 pandemic era, can be helped. Therefore, the management of zakat management organizations such as the Regency BAZNAS must be able to integrate, interact and innovate the management of zakat funds, productive infaq and shadaqah and program linkage with the government in the Covid-19 Pandemic Era in the Kab. Jember. The purpose of this study is to analyze the model of integration, interaction, innovation, and implementation of the management of zakat, infaq and productive shadaqah funds through linkage programs during the Covid-19 pandemic era. This study uses a quantitative approach (explanatory research) which is strengthened by qualitative (constructive research).